1990
DOI: 10.1115/1.2891998
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Material Properties on the Stability of Static Thermoelastic Contact

Abstract: When heat is conducted across an interface between two different materials, the interaction between thermoelastic distortion and thermal contact resistance can cause the system to be unstable. This paper investigates the influence of material properties on the stability criterion for an interface between two half planes. It is found that most material combinations exhibit one or other of two kinds of stability behavior. In one of these, the stability criterion is closely related to that for uniqueness of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 9 publications
0
29
0
Order By: Relevance
“…In such cases, disturbance of the system from an unstable steady-state will cause it to gravitate towards an alternative stable state. However, for some material combinations, instability can occur for sufficiently high heat fluxes in both directions (Zhang and Barber, 1990) and unique steady states can be unstable (Zhang and Barber, 1993). A different category of thermoelastic contact instability can occur if there is sliding between the contacting bodies, in which case the work done against frictional tractions leads to localized heating proportional to the local contact pressure.…”
Section: Introductionmentioning
confidence: 99%
“…In such cases, disturbance of the system from an unstable steady-state will cause it to gravitate towards an alternative stable state. However, for some material combinations, instability can occur for sufficiently high heat fluxes in both directions (Zhang and Barber, 1990) and unique steady states can be unstable (Zhang and Barber, 1993). A different category of thermoelastic contact instability can occur if there is sliding between the contacting bodies, in which case the work done against frictional tractions leads to localized heating proportional to the local contact pressure.…”
Section: Introductionmentioning
confidence: 99%
“…We next consider a tube in which the inner and outer cylinders are of nickel alloy and magnesium alloy, respectively, which defines a Type 2 interface in the classification of Zhang and Barber [7]. Figure 5 shows the dimensionless heat flux at which a zero crosses into the right half-plane as a function of wavenumber n for the case 1 -71 = ?z -1 = 0.05, R* = 1.…”
Section: Magnesium Alloy/nickel Alloy Interfacementioning
confidence: 99%
“…For dissimilar materials, Zhang and Barber [7] showed that qualitatively distinct kinds of thermoelastic stability behaviour are obtained for the contact of two half-planes, depending on the relative values of the material property ratios defined in Eqn (38). The finite geometry of the duplex tube can be expected to modify this behaviour [17], but Zhang and Barber's classification of material pairs provides a useful starting point in exploring the behaviour of this more complex system.…”
Section: Dissimilar Materialsmentioning
confidence: 99%
See 2 more Smart Citations